Quality of individualized education program goals of preschoolers with disabilities - Silva, Tânia Carina Boavida Domingues da (2012)
Individualized education programs (IEPs) are a fundamental mechanism for making special education services unique for the child and for enhancing the developmental outcomes of children with disabilities. If written IEP goals diverge, however, from recommended practices, they might result in ineffective interventions. This study investigated the quality of Portuguese IEP goals written for 83 preschoolers with disabilities attending public preschool classrooms from 21 school groups from the District of Lisbon, Portugal. The quality of IEP goals was measured using the Goal Functionality Scale III (R. A. McWilliam, 2009) and the IEP/Individualized Family Service Plan Goals and Objectives Rating Instrument (A. R. Notari, 1988). Results showed that IEP goals were too broad, lacked functionality and measurability, and did not appropriately address skills within the context of natural routines and settings. Moreover, findings indicate that measurability was slightly higher the more severe the children’s disabilities were and that autonomy (ie, self-help) goals were somewhat more functional and measurable than were social, language, cognitive, and motor goals. Findings raise concerns about the effectiveness of interventions based on such goals in enhancing children’s developmental outcomes and suggest the need for clear guidelines on the development of effective IEPs and teacher training on developing high-quality goals.